Effectiveness of dietary supplements for skin photoaging in healthy adults: a systematic review and meta-analysis of randomized controlled trials - Qifeng Yang; Haoying Li; Hanxin Zhang; Luyao Ma; Xiaofeng Zhang; Jingping Wu (Frontiers in Medicine, 2025)
BackgroundThe dietary supplement industry offers a wide range of orally consumed products that claim to combat skin photoaging, however, there is a lack of research on the proof of safety and effectiveness of dietary supplements in anti-skin photoaging. To further confirm their safety and efficacy, this article provides a detailed review and meta-analysis.MethodsFour databases, including PubMed, Embase, Web of Science, and the Cochrane Library (Central Database), were searched for relevant literature up to October 2024. A total of forty English-language randomized controlled trials (RCTs) investigating the relationship between dietary supplements and skin photoaging were screened for an in-depth review and meta-analysis.ResultsCollagen, flavanols, and other polyphenol supplements have been found to alleviate skin photoaging and increase MED or overall skin elasticity (R2) when compared to a placebo. However, hyaluronic acid, lycopene, and carotenoids did not show any significant benefits in improving skin photoaging or MED/R2. Due to inconsistent findings and limited research, the effects of dietary supplements on skin photoaging could not be determined in randomized controlled trials with two or fewer studies. It is important to note that, during the study period (typically ≤ 24 weeks), all orally administered dietary supplements were found to be safe.ConclusionOral dietary supplements, such as collagen, flavanols, and polyphenols, have demonstrated effectiveness in addressing skin photoaging. However, there is currently insufficient evidence to support the recommendation of other dietary supplements, such as astaxanthin, for the treatment of skin photoaging. This research serves as an initial step in exploring the benefits of dietary supplements in combating skin photoaging. It underscores the need for more focused studies to further investigate the effects of dietary supplements on skin photoaging and gather additional evidence supporting their efficacy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023472473, identifier CRD42023472473.